Zirconia composite oxide powder and method for producing the zirconia composite oxide powder

By adjusting the ratio of zirconium and rare earth element oxides and controlling the pore distribution, a zirconium-based composite oxide powder with a particle size of less than 1.0 μm and having a good pore structure was prepared, which solved the problems of excessive particle size of the powder and insufficient pore structure in the prior art, and improved its adsorption efficiency in GPF.

JP7649417B1Active Publication Date: 2025-03-19DAIICHI KIGENSO KAGAKU KOGYO CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024215323
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-19
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

In the prior art, the zirconium-based composite oxide powder has an excessive particle size in the cylinder filter (GPF) and lacks sufficient pore structure, resulting in low adsorption efficiency in the exhaust gas.

Method used

By adjusting the ratio of zirconium and rare earth element oxides, the content of zirconium is controlled between 50% and 95%, and the pore distribution is measured by small-angle X-ray scattering method to ensure that the pore distribution is a single-peak distribution within the range of 1 nm to 15 nm, and the preparation of zirconium-based composite oxide powder with a particle size less than 1.0 μm is achieved.

Benefits of technology

The prepared zirconium-based composite oxide powder has a small particle size, a low pore volume and a good pore structure, which improves its adsorption efficiency in GPF and its performance in exhaust gases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649417000001_ABST
    Figure 0007649417000001_ABST
Patent Text Reader

Abstract

To provide a porous zirconia composite oxide powder having a small particle size and a small pore volume. The present invention relates to a method for producing a zirconia-based powder comprising the steps of: (a) providing a powder containing zirconia and an oxide of a rare earth element; (b) providing a powder containing zirconia in an amount of 50% by weight or more and 95% by weight or less; (c) providing a powder containing zirconia in an amount of 50% by weight or more and 95% by weight or less; (d) providing a powder containing zirconia in an amount of 50% by weight or more and 95% by weight or less; (e) providing a powder containing zirconia in an amount of 50% by weight or more and 95% by weight or less; (f) providing a powder containing zirconia in an amount of 50% by weight or more and 95% by weight or less; (g) providing a powder containing zirconia in an amount of 50% by weight or more and 95% by weight or less; 50 is 0.05 μm or more and less than 1.0 μm, and the tap density is 1.0 g / cm 3 More than 1.7g / cm 3 The zirconia-based composite oxide powder has a crystal system as identified by powder X-ray diffraction, which is either a tetragonal system, a cubic system, or both.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a zirconia-based composite oxide powder and a method for producing the zirconia-based composite oxide powder. [Background technology]

[0002] Currently, direct injection is the mainstream for gasoline engines, and exhaust gas purification catalysts that combine gasoline particulate filters (GPFs) with three-way catalyst (TWC) functions are used to capture and purify particulate matter (PM). TWCs are supported on and inside the GPFs, and zirconia-based composite oxides that support fine particles of precious metals such as Pt, Rh, and Pd are often used as TWCs.

[0003] Particle size D 50 Patent Documents 1 to 4 disclose zirconia-based composite oxides having a particle size of 1 μm or less.

[0004] Patent Document 1 discloses a fine zirconia powder containing one or more of yttria, calcia, magnesia, and ceria as a stabilizer, the fine zirconia powder having an average particle size of less than 0.5 μm and in which the proportion of particles at 1 μm in a cumulative curve of particle size distribution is 100% (Claim 1).

[0005] Patent Document 2 describes a sintered body containing a stabilizer and having a specific surface area of ​​20 m 2 / g or more 60m 2 / g or less, and the particle size D 50 The zirconia powder disclosed has a diameter of 0.1 μm or more and 0.7 μm or less, a peak top diameter of a pore volume distribution of 20 nm or more and 85 nm or less in the range of 10 nm or more and 200 nm or less in a pore distribution based on mercury intrusion porosimetry, a pore volume of 0.2 ml / g or more and less than 0.5 ml / g, and a pore distribution width of 40 nm or more and 105 nm or less (Claim 1).

[0006] Patent Document 3 describes a method for producing a sintered body containing a stabilizer, the stabilizer being CaO, Y 2 O 3 , Er2 O 3 or Yb 2 O 3 and the specific surface area is 10m 2 / g or more 50m 2 / g or less, and the particle size D 50 A zirconia powder having a particle size of 0.1 μm or more and 0.7 μm or less is disclosed (claim 1 and claim 2).

[0007] In Patent Document 4, the pore volume in the pore diameter distribution obtained by mercury intrusion porosimetry is defined as Vp X-Y When [(Vp 10-100 ) / (Vp 100-6000 )] satisfies the following formula [1], and the particle diameter after the crushing process D 50 However, a zirconia-based powder material having a particle size of 0.05 μm or more and 1.5 μm or less is disclosed (claim 1, claim 7). Formula [1] 0.4≦[(Vp 10-100 ) / (Vp 100-6000 )]≦1 [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2006-240928 A [Patent Document 2] International Publication No. 2022 / 075345 [Patent Document 3] International Publication No. 2022 / 075346 [Patent Document 4] JP 2023-142376 A Summary of the Invention [Problem to be solved by the invention]

[0009] What is required for the zirconia-based composite oxide to be supported inside the GPF is a porous powder having a small particle size and a small pore volume. By reducing the particle size of the zirconia-based composite oxide, it becomes possible to favorably support it inside the GPF. In addition, by making the zirconia-based composite oxide a porous body, it is possible to increase the frequency of contact with exhaust gas. In addition, since there is an upper limit to the amount of zirconia-based composite oxide that can be supported on the GPF, by reducing the pore volume of the zirconia-based composite oxide, it is possible to support more zirconia-based composite oxide on the GPF.

[0010] However, although the zirconia fine powder in Patent Document 1 is said to have a particle size distribution cumulative curve in which the proportion of particles of 1 μm is 100%, the specific surface area is 15 m 2 / g (see Examples), it is believed that the powder contains a certain proportion of non-porous particles that do not have pores.

[0011] Furthermore, as is clear from FIG. 2 of Patent Document 2, the zirconia powder of Patent Document 2 has no peak in the range of 1 nm or more and 15 nm or less in the pore distribution, and therefore cannot be said to be porous.

[0012] Furthermore, as is clear from Figs. 2 and 3 of Patent Document 3, the zirconia powder of Patent Document 3 has no peak in the range of 1 nm or more and 15 nm or less in the pore distribution, and therefore cannot be said to be porous.

[0013] Furthermore, it is stated in Patent Document 4 that the zirconia-based powder material has excellent crushability because the pore volume derived from tertiary particle agglomerates of 100 to 6000 nm is a constant ratio to the pore volume derived from secondary particle agglomerates of 10 to 100 nm (paragraph

[0010] ). In other words, the zirconia-based powder material in Patent Document 4 is a bulky powder having relatively large pores that are easily crushed starting from the pores, and has a large pore volume.

[0014] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a porous zirconia-based composite oxide powder having a small particle size and a small pore volume, and to provide a method for producing the zirconia-based composite oxide powder by which the zirconia-based composite oxide powder can be obtained. [Means for solving the problem]

[0015] The present inventors have conducted extensive research into the above-mentioned problems, and as a result have succeeded in producing a porous zirconia-based composite oxide powder having a small particle size and a small pore volume, thereby completing the present invention.

[0016] That is, the present invention provides the following. [1] Zirconia and Oxides of rare earth elements Including, The content of the zirconia is 50% by weight or more and 95% by weight or less, The pore size distribution calculated from the scattering curve measured by small angle X-ray scattering has a monomodal distribution in the range of 1 nm to 15 nm. Particle diameter D in the particle size distribution measured by the laser diffraction / scattering method 50 is 0.05 μm or more and less than 1.0 μm, Tap density is 1.0g / cm 3 More than 1.7g / cm 3 is as follows: A zirconia-based composite oxide powder, characterized in that the crystal system identified by powder X-ray diffraction is either a tetragonal system, a cubic system, or both.

[0017] According to the above-mentioned configuration, the composite oxide contains zirconia and an oxide of a rare earth element. Conventionally, a composite oxide of zirconia and an oxide of a rare earth element is prone to aggregation during production, and fine particles (particle diameter D 50 However, in the present invention, a composite oxide containing zirconia and an oxide of a rare earth element has a particle diameter D 50It was possible to obtain a zirconia-based composite oxide powder with a small particle size of less than 1.0 μm. Moreover, according to the above-mentioned configuration, since the material contains zirconia and an oxide of a rare earth element, it is suitable for use as a catalyst.

[0018] According to the above-mentioned configuration, the tap density is 1.0 g / cm 3 For these reasons, it can be said that the pore volume is sufficiently small. As described later, the zirconia-based composite oxide powder of the present invention is porous, but has a small pore size (having a monomodal distribution in the range of 1 nm to 15 nm), so that although it is porous, the pore volume is small.

[0019] According to the above-mentioned configuration, the pore size distribution calculated from the scattering curve measured by the small angle X-ray scattering method has a monomodal distribution in the range of 1 nm to 15 nm. 50 In particles with a diameter of less than 1.0 μm, the pore size distribution is monomodal in the range of 1 nm to 15 nm, and therefore the particles (secondary particles) have uniform pores inside, i.e., they are porous. For example, as in Comparative Example 2 shown in FIG. 2, when the pore distribution has two peaks in the range of 1 nm to 15 nm, that is, when the pore distribution is bimodal rather than monomodal, such a pore distribution is a pore distribution specific to particles subjected to wet pulverization. The peak at about 14 nm in FIG. 2 is derived from the pores inside the particles (secondary particles), while the peak at about 3 nm in FIG. 2 is derived from the particles (particles themselves without pores) produced by wet pulverization. Therefore, when the pore distribution in the range of 1 nm to 15 nm is bimodal, the pores inside the particles (secondary particles) are few and cannot be said to be porous. The phrase "having a monomodal distribution in the range of 1 nm or more and 15 nm or less" means that the pore distribution curve has only one peak in the range of 1 nm or more and 15 nm or less.

[0020] When zirconia contains a certain amount of rare earth element, it does not contain monoclinic crystals and has only tetragonal and cubic crystals. According to the above-mentioned configuration, the crystal system identified by powder X-ray diffraction is either tetragonal or cubic, or both, so that it contains rare earth element and is suitable for use as a catalyst.

[0021] Since the zirconia fine powder of Patent Document 1 is produced by wet milling, even if it has a peak in the pore distribution in the range of 1 nm or more and 15 nm or less, it is highly likely that it has two peaks, and it cannot be said to have a monomodal distribution in the range of 1 nm or more and 15 nm or less. Moreover, the zirconia powders of Patent Documents 2 and 3 do not have even one peak in the range of 1 nm or more and 15 nm or less in the pore distribution, and therefore cannot be said to be porous.

[0022] As described above, according to the above-mentioned configuration, it is possible to provide a porous zirconia-based composite oxide powder which is a composite oxide containing zirconia and an oxide of a rare earth element, and has a small particle size and a small pore volume.

[0023] Furthermore, the present invention provides the following: [2] The zirconia composite oxide powder according to [1] above, having pores within each particle.

[0024] Whether or not a single particle has a pore is determined by the following <Procedures> a to f using an HAADF-STEM image. In a HAADF-STEM image, the detected signal is converted into a brightness value with 256 levels (0 to 255) per pixel to create a single image, with empty space appearing dark (low brightness value) and areas where matter exists appearing bright (high brightness value). The brightness value of an area where matter exists correlates with the electron density of that area, and the higher the electron density, the brighter it appears. In materials made up of the same constituent elements, the electron density is the same as the density of the material, and when contrast is confirmed within the particle, the dark areas are areas of low material density and can be said to be pores. The presence or absence of pores can be confirmed, for example, by the following procedure using image analysis software such as ImageJ. <Procedure> a. Take a HAADF-STEM image at 2 million times magnification or more. b. Convert to grayscale (8-bit) using image analysis software. c. Areas with a brightness value of 80 or more, expressed in 256 levels from 0 to 255, are determined to be areas containing particles, and one spherical particle (single particle) with no overlapping particles is extracted. d. Within the extracted particles, regions with a long axis of 1 nm or more where the brightness value is 40% or more lower than the surrounding area are considered to be pores, and their presence or absence is confirmed. e. Repeat until the cumulative number of particles confirmed to have pores reaches 100. f. If it is confirmed by steps a to e that all particles have pores, it is determined that "a single particle has a pore." When pores are found within particles in the HAADF-STEM image observation according to the above-mentioned <Procedure>, this means that the pores in the zirconia-based composite oxide powder are not voids (interparticle gaps) between particles, but voids that are contained within the particles themselves.

[0025] Furthermore, the present invention provides the following: [3] The particle diameter D 50 The zirconia composite oxide powder according to [1] or [2] above, characterized in that the particle size is 0.08 μm or more and 0.85 μm or less.

[0026] The particle diameter D 50 When the particle diameter is 0.85 μm or less, it can be said that the particle diameter (particle diameter of secondary particles) is smaller.

[0027] Furthermore, the present invention provides the following: [4] Specific surface area is 30m 2 / g or more 90m 2 The zirconia composite oxide powder according to any one of the above [1] to [3], characterized in that the zirconia composite oxide powder has a viscosity of less than 1000 mg / g.

[0028] Specific surface area is 30m 2 / g or more, it can be said to be more porous. 2When the pore volume is less than 1 / g, the pore volume can be made smaller.

[0029] Furthermore, the present invention provides the following: [5] The rare earth element oxide is at least one selected from the group consisting of yttrium oxide, lanthanum oxide, cerium oxide, neodymium oxide, and praseodymium oxide; The zirconia composite oxide powder according to any one of [1] to [4] above, characterized in that the content of the oxide of the rare earth element is 5% by weight or more and 50% by weight or less.

[0030] When the oxide of the rare earth element is one or more selected from the group consisting of yttrium oxide, lanthanum oxide, cerium oxide, neodymium oxide, and praseodymium oxide, and the content of the oxide of the rare earth element is 5% by weight or more and 50% by weight or less, it is more suitable for use as a catalyst.

[0031] Furthermore, the present invention provides the following: [6] A step 1 of adjusting the pH of an aqueous solution of zirconium oxychloride to form a suspension; The pH of the suspension is made lower than that of step 1, and the suspension is heated to obtain hydrated ZrO 2 Step 2 of obtaining a microcrystal nucleus slurry; Hydrated ZrO 2 Adding a flocculant to the micro-crystal nucleus slurry produces hydrated ZrO. 2 Step 3 of obtaining a zirconium sulfate-containing basic slurry; Hydrated ZrO 2 Step 4 of adding a surface modifier to the zirconium sulfate-containing basic slurry; Step 5 of adding a raw material salt containing a rare earth element; Step 6: neutralizing with a base to obtain a precipitate; a step 7 of obtaining a zirconia-based composite oxide by heat-treating the precipitate; The method for producing a zirconia composite oxide powder according to any one of the above [1] to [5], comprising:

[0032] According to the above-mentioned configuration, the pH of the suspension is made lower than that of the step 1, and the suspension is heated to obtain hydrated ZrO 2 To obtain a fine crystal nucleus slurry (step 2), the particles can be porous but have a small pore volume with a peak in the pore size distribution in the range of 1 nm or more and 15 nm or less.

[0033] According to the above-mentioned configuration, hydrated ZrO 2 Adding a flocculant to the micro-crystal nucleus slurry produces hydrated ZrO. 2 In order to obtain a zirconium sulfate-containing basic slurry (step 3), secondary particles having strong agglomerations between primary particles are obtained.

[0034] According to the above-mentioned configuration, hydrated ZrO 2 Since a surface modifier is added to the zirconium sulfate-containing basic slurry and then a rare earth element is added (step 5), aggregation of secondary particles during firing (step 7) can be suppressed.

[0035] As described above, according to the above-mentioned method, a porous zirconia composite oxide powder having a small particle size and a small pore volume can be obtained. Effect of the Invention

[0036] According to the present invention, it is possible to provide a porous zirconia-based composite oxide powder having a small particle size and a small pore volume, and also to provide a method for producing the zirconia-based composite oxide powder by which the zirconia-based composite oxide powder can be obtained. [Brief description of the drawings]

[0037] [Figure 1] 3 shows the pore distribution of Example 1 and Example 2. [Diagram 2] 3 shows the pore distributions of Comparative Example 1 and Comparative Example 2. [Diagram 3] 1 shows an HAADF-STEM image of Example 1. [Figure 4] 1 shows a HAADF-STEM image of Example 2. [Diagram 5]1 is a HAADF-STEM image of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] Hereinafter, the embodiments of the present invention will be described. However, the present invention is not limited to these embodiments. In this specification, the zirconia-based composite oxide powder is a general one that contains impurity metal compounds of 10 mass% or less in terms of oxide including hafnium. In addition, in this specification, the expressions "contain" and "include" include the concepts of "contain", "include", "substantially consists of" and "consist only of".

[0039] The maximum and minimum values ​​of the content of each component shown below are independently the preferred minimum and maximum values ​​of the present invention, regardless of the contents of other components. Furthermore, the maximum and minimum values ​​of various parameters (measured values, etc.) shown below are independently preferred minimum and maximum values ​​of the present invention, regardless of the content (composition) of each component.

[0040] [Zirconia-based composite oxide powder] The zirconia composite oxide powder according to this embodiment is Zirconia and Oxides of rare earth elements Including, The content of the zirconia is 50% by weight or more and 95% by weight or less, The pore size distribution calculated from the scattering curve measured by small angle X-ray scattering has a monomodal distribution in the range of 1 nm to 15 nm. Particle diameter D in the particle size distribution measured by the laser diffraction / scattering method 50 is 0.05 μm or more and less than 1.0 μm, Tap density is 1.0g / cm 3 More than 1.7g / cm 3 is as follows: The crystal system, as identified by powder X-ray diffraction, is either tetragonal, cubic, or both.

[0041] As described above, the zirconia-based composite oxide powder according to the present embodiment contains zirconia and an oxide of a rare earth element. The zirconia-based composite oxide powder may be composed only of zirconia and an oxide of a rare earth element, or may contain other components as long as the effects of the present invention are achieved (as long as the effects of the present invention are not significantly hindered). Conventionally, composite oxides of zirconia and rare earth oxides are prone to aggregation during production, and fine particles (particle diameter D 50 However, in the present embodiment, a composite oxide containing zirconia and an oxide of a rare earth element has a particle diameter D 50 It was possible to obtain a zirconia-based composite oxide powder with a small particle size of less than 1.0 μm. The zirconia-based composite oxide powder according to this embodiment contains zirconia and an oxide of a rare earth element, and is therefore suitable for use as a catalyst.

[0042] The content of the zirconia is 50% by weight or more and 95% by weight or less based on the total weight of the zirconia-based composite oxide powder. The zirconia content is from 50% by weight to 95% by weight, making it suitable for use as a catalyst.

[0043] The content of the zirconia is preferably 52 mass % or more, and more preferably 54 mass % or more, based on the total amount of the zirconia-based composite oxide powder. The content of the zirconia is preferably 94 mass % or less, and more preferably 93 mass % or less, based on the total mass of the zirconia-based composite oxide powder. The content of the zirconia is preferably from 52% by mass to 94% by mass, and more preferably from 54% by mass to 94% by mass, based on the total mass of the zirconia-based composite oxide powder.

[0044] The content of the rare earth element oxide is preferably 5% by weight or more and 50% by weight or less based on the total weight of the zirconia-based composite oxide powder. When the content of the rare earth element oxide is 5% by weight or more and 50% by weight or less, it is more suitable for use as a catalyst.

[0045] The content of the rare earth element oxide is more preferably 6 mass % or more, and further preferably 7 mass % or more, based on the entire zirconia composite oxide powder. The content of the rare earth element oxide is more preferably 48 mass % or less, and further preferably 46 mass % or less, based on the total mass of the zirconia-based composite oxide powder. The content of the rare earth element oxide is more preferably 6 mass % or more and 48 mass % or less, and further preferably 7 mass % or more and 46 mass % or less, based on the entire zirconia-based composite oxide powder.

[0046] The zirconia-based composite oxide powder preferably contains at least one oxide selected from the group consisting of yttrium oxide, lanthanum oxide, cerium oxide, neodymium oxide, and praseodymium oxide, among oxides of rare earth elements. The rare earth element oxide is more preferably at least one oxide selected from the group consisting of yttrium oxide, lanthanum oxide, cerium oxide, neodymium oxide, and praseodymium oxide for use as a catalyst.

[0047] The total content of the zirconia and the oxide of the rare earth element is preferably 85 mass % or more based on the entire zirconia-based composite oxide powder. When the total content of the zirconia and the oxide of the rare earth element is 85 mass % or more, it is suitable for use as a catalyst.

[0048] The total content of the zirconia and the oxide of the rare earth element is more preferably 88% by mass or more, and further preferably 90% by mass or more, based on the zirconia-based composite oxide powder. The total content of the zirconia and the oxide of the rare earth element may be 100 mass %, 99 mass % or less, or 98 mass % or less, based on the zirconia-based composite oxide powder. The total content of the zirconia and the oxide of the rare earth element is more preferably 88% by mass or more and 100% by mass or less, and further preferably 90% by mass or more and 100% by mass or less, based on the zirconia-based composite oxide powder.

[0049] The zirconia-based composite oxide powder may contain one or more oxides selected from the group consisting of (A) an oxide of at least one element selected from the group consisting of In, Si, Sn, Bi, P, and Zn, (B) a transition metal oxide (excluding oxides of rare earth elements and oxides of precious metal elements), and (C) an alkaline earth metal oxide. These components (A) to (C) are hereinafter also referred to as "other oxides".

[0050] The transition metal oxide may be one or more oxides selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ta and W.

[0051] The alkaline earth metal oxide may be one or more oxides selected from the group consisting of Mg, Ca, Sr and Ba.

[0052] When the zirconia-based composite oxide powder contains the other oxides, the content of the other oxides is preferably 0.5% by mass or more and 25% by mass or less based on the entire zirconia-based composite oxide powder.

[0053] The content of the other oxides is more preferably 1% by mass or more, and further preferably 1.5% by mass or more, based on the total mass of the zirconia composite oxide powder. The content of the other oxides is more preferably 15% by mass or less, further preferably 10% by mass or less, and particularly preferably 5% by mass or less, based on the total amount of the zirconia composite oxide powder. The content of the other oxides is more preferably from 1 mass % to 15 mass %, and further preferably from 1.5 mass % to 10 mass %, based on the entire zirconia composite oxide powder.

[0054] The zirconia composite oxide powder has a particle diameter D 50 is 0.05 μm or more and less than 1.0 μm. 50 Since the particle size is less than 1.0 μm, the particle size is small and is suitable for use as a catalyst.

[0055] The particle diameter D 50 is preferably 0.90 μm or less, more preferably 0.85 μm or less. The particle diameter D 50 is not particularly limited, but is, for example, 0.07 μm or more, 0.08 μm or more, etc. The particle diameter D 50 is preferably 0.07 μm or more and 0.90 μm or less, and more preferably 0.08 μm or more and 0.85 μm or less.

[0056] The zirconia composite oxide powder has a particle diameter D 90 It is preferable that the particle diameter D is 0.08 μm or more and 1.6 μm or less. 90 When the particle size is 1.6 μm or less, there are no large particles and the particle size of the whole particles is small, which is suitable for use as a catalyst.

[0057] The particle diameter D 90 is more preferably 1.5 μm or less, and further preferably 1.4 μm or less. The particle diameter D 90 is not particularly limited, but is, for example, 0.1 μm or more, 0.11 μm or more, etc. The particle diameter D 90 is more preferably 0.1 μm or more and 1.5 μm or less, and further preferably 0.11 μm or more and 1.4 μm or less.

[0058] The particle diameter D 50 , the particle diameter D 90 is a value obtained by the method described in the Examples.

[0059] The zirconia composite oxide powder has a monomodal distribution in the range of 1 nm to 15 nm in terms of pore size distribution calculated from a scattering curve measured by small angle X-ray scattering. The zirconia composite oxide powder has a particle diameter D 50 The particle diameter is less than 1.0 μm, and the pore size distribution is monomodal in the range of 1 nm to 15 nm. Therefore, the particle (secondary particle) has uniform pores inside, i.e., it can be said to be porous.

[0060] The zirconia-based composite oxide powder has a monomodal distribution in the range of 1 nm to 15 nm in the pore distribution calculated from a scattering curve measured by small-angle X-ray scattering, and may or may not have a peak in the range of more than 15 nm to 40 nm. From the viewpoint of reducing the pore volume, it is preferable that there is no peak in the range of more than 15 nm to 40 nm.

[0061] The pore distribution is determined by the method described in the Examples.

[0062] The zirconia composite oxide powder preferably has no pores in the range exceeding 40 nm in the pore distribution.

[0063] The zirconia composite oxide powder has a tap density of 1.0 g / cm 3 More than 1.7g / cm 3 The tap density is 1.0 g / cm or less. 3 Since the tap density is 1.7 g / cm or more, the pore volume can be said to be sufficiently small. 3 Since the above ratio is smaller than 1, it can be said that the particles are porous.

[0064] The tap density is preferably 1.03 g / cm 3 More preferably, 1.05 g / cm 3 That's all. The tap density is preferably 1.69 g / cm 3 Less than or equal to 1.68 g / cm 3 The following is the result. The tap density is preferably 1.03 g / cm 3 More than 1.69g / cm 3 Less than or equal to 1.05 g / cm 3 More than 1.68g / cm 3 The following is the result.

[0065] The tap density is a value obtained by the method described in the Examples.

[0066] The zirconia composite oxide powder has a bulk density of 0.5 g / cm 3 More than 1.2g / cm 3 It is preferable that the bulk density is 0.5 g / cm or less. 3 If the bulk density is 1.2 g / cm or more, the pore volume is sufficiently small. 3 If it is below this, it can be said to be a porous particle.

[0067] The bulk density is more preferably 0.52 g / cm 3 More preferably, 0.54 g / cm 3 That's all. The bulk density is more preferably 1.1 g / cm 3 More preferably, 1.0 g / cm 3 The following is the result. The bulk density is more preferably 0.52 g / cm 3 More than 1.1g / cm 3 More preferably, 0.54 g / cm 3 More than 1.0g / cm 3 The following is the result.

[0068] The bulk density is a value obtained by the method described in the Examples.

[0069] The zirconia composite oxide powder has a crystal system, which is identified by powder X-ray diffraction, of either a tetragonal system or a cubic system, or both. When zirconia contains a certain amount of rare earth elements, it does not contain monoclinic crystals, but only tetragonal and cubic crystals. The crystal system identified by powder X-ray diffraction is either tetragonal or cubic, or both, so it contains rare earth elements and is suitable for use as a catalyst.

[0070] The zirconia composite oxide powder has a specific surface area of ​​30 m 2 / g or more 90m 2 It is preferable that the molecular weight is less than 1 / g. Specific surface area is 30m 2 / g or more, it can be said to be more porous. 2 When the pore volume is less than 1 / g, the pore volume can be made smaller.

[0071] The specific surface area is more preferably 32 m 2 / g or more, more preferably 34m 2 / g or more. The specific surface area is more preferably 85 m 2 / g or less, more preferably 82m 2 / g or less. The specific surface area is more preferably 32 m 2 / g or more 85m 2 / g or less, more preferably 34m 2 / g or more 82m 2 / g or less.

[0072] The specific surface area is a value obtained by the method described in the Examples.

[0073] The zirconia composite oxide powder preferably has pores within each particle. Whether or not a single particle has pores is determined by the following <Procedures> a to f using an HAADF-STEM image. <Procedure> a. Take a HAADF-STEM image at 2 million times magnification or more. b. Convert to grayscale (8-bit) using image analysis software. c. Areas with a brightness value of 80 or more, expressed in 256 levels from 0 to 255, are determined to be areas containing particles, and a single spherical particle with no overlapping particles is extracted. d. Within the extracted particles, regions with a long axis of 1 nm or more where the brightness value is 40% or more lower than the surrounding area are considered to be pores, and their presence or absence is confirmed. e. Repeat until the cumulative number of particles confirmed to have pores reaches 100. f. If it is confirmed by steps a to e that all particles have pores in them, it is determined that the particles have pores in them. When pores are found within particles in the HAADF-STEM image observation according to the above-mentioned <Procedure>, this means that the pores in the zirconia-based composite oxide powder are not voids (interparticle gaps) between particles, but voids that are contained within the particles themselves.

[0074] When the zirconia-based composite oxide powder is used as a catalyst support for an exhaust gas purification catalyst, the metal to be supported is not particularly limited, but examples thereof include Pt, Pd, and Rh.

[0075] [Method of manufacturing zirconia-based composite oxide powder] An example of a method for producing a zirconia composite oxide powder will be described below, however, the method for producing a zirconia composite oxide powder of the present invention is not limited to the following example.

[0076] The method for producing the zirconia composite oxide powder according to the present embodiment includes the steps of: A step 1 of adjusting the pH of an aqueous solution of zirconium oxychloride to form a suspension; The pH of the suspension is made lower than that of step 1, and the suspension is heated to obtain hydrated ZrO 2 Step 2 of obtaining a microcrystal nucleus slurry; Hydrated ZrO 2 Adding a flocculant to the micro-crystal nucleus slurry produces hydrated ZrO. 2 Step 3 of obtaining a zirconium sulfate-containing basic slurry; Hydrated ZrO 2 Step 4 of adding a surface modifier to the zirconium sulfate-containing basic slurry; Step 5 of adding a raw material salt containing a rare earth element; Step 6: neutralizing with a base to obtain a precipitate; a step 7 of obtaining a zirconia-based composite oxide by heat-treating the precipitate; Includes.

[0077] Hereinafter, each step of the method for producing the zirconia composite oxide powder according to this embodiment will be described.

[0078] First, the pH of an aqueous solution of zirconium oxychloride is adjusted to form a suspension (step 1).

[0079] The concentration of the zirconium oxychloride aqueous solution is ZrO 2 Concentration is 2% by weight or more It is sufficient to use one having a content of 15% by weight or less.

[0080] In step 1, the pH is preferably adjusted to 2 or more and 7 or less.

[0081] The pH of the aqueous zirconium oxychloride solution obtained by dissolving zirconium oxychloride in water is usually less than 2, so the pH can be adjusted to 2 or more by adding a base to the aqueous zirconium oxychloride solution.

[0082] In step 1, the pH is preferably adjusted to more preferably 2.5 or higher, and even more preferably 2.7 or higher. In step 1, the pH is more preferably adjusted to 6.5 or less, and even more preferably 6 or less. In step 1, the pH is more preferably adjusted to 2.5 or more and 6.5 or less, and further preferably 2.7 or more and 6 or less.

[0083] Examples of the base include alkali hydroxides such as sodium hydroxide and potassium hydroxide, aqueous ammonia, etc. Among these, sodium hydroxide (aqueous sodium hydroxide solution) is preferred from the viewpoints of basicity and availability.

[0084] In step 1, by adjusting the pH to 2 or more and 7 or less, the zirconium salt dissolved in the aqueous solution can be suitably precipitated as zirconium hydroxide, and a suspension of zirconium hydroxide can be suitably obtained. Note that the zirconium hydroxide in the suspension is not crystallized and is amorphous. If the pH is made too high in step 1 (for example, 8 or higher), the salt concentration may become too high when an acid is added in the subsequent step (step 2), which may interfere with the reaction. For example, if a large amount of aqueous sodium hydroxide solution is used to adjust the pH in step 1 and then a large amount of hydrochloric acid is added in step 2, the NaCl concentration may become high, which may interfere with the reaction.

[0085] Next, the pH of the suspension is reduced to a value lower than that of step 1, and the suspension is heated to obtain hydrated ZrO 2 A microcrystal nucleus slurry is obtained (Step 2).

[0086] In step 2, the pH value of the suspension is not particularly limited as long as it is made lower than that of step 1, but it is preferable to adjust the pH to 1 or more and 1.5 or less. By adjusting the pH to 1 or more and 1.5 or less, hydrated ZrO 2 A fine crystal nucleus slurry can be suitably obtained. That is, by adjusting the pH to the boundary where zirconium hydroxide cannot be dissolved in the aqueous solution, hydrated ZrO 2 A fine crystal nucleus slurry can be obtained. If the pH is too low, precipitation occurs all at once, and hydrated ZrO 2 There is a risk that an amorphous body will be generated instead of the crystal nuclei.

[0087] In step 2, the pH is preferably adjusted to more preferably 1.1 or higher, and even more preferably 1.15 or higher. In step 2, the pH is more preferably adjusted to 1.4 or less, and even more preferably to 1.35 or less. In step 2, the pH is more preferably adjusted to 1.1 or more and 1.4 or less, and further preferably 1.15 or more and 1.35 or less.

[0088] In step 2, the heating temperature is preferably 90°C or higher and 120°C or lower. By setting the heating temperature to 90° C. or higher and 120° C. or lower, hydrated ZrO 2 A fine crystal nucleus slurry can be advantageously obtained.

[0089] The heating temperature in step 2 is more preferably 95° C. or higher, and further preferably 98° C. or higher. The heating temperature in step 2 is more preferably 115° C. or lower, and further preferably 110° C. or lower. The heating temperature in step 2 is more preferably 95°C or higher and 115°C or lower, and further preferably 98°C or higher and 110°C or lower.

[0090] In step 2, the heating time is preferably 140 hours or more and 200 hours or less. By setting the heating time to 140 hours or more and 200 hours or less, hydrated ZrO 2 A fine crystal nucleus slurry can be advantageously obtained.

[0091] The heating time in step 2 is more preferably 150 hours or more, and further preferably 155 hours or more. The heating time in step 2 is more preferably 190 hours or less, and even more preferably 185 hours or less. The heating time in step 2 is more preferably from 150 hours to 190 hours, and further preferably from 155 hours to 185 hours.

[0092] In step 2, the pH of the suspension is made lower than that in step 1, and the suspension is heated to obtain hydrated ZrO 2 In order to obtain a fine crystal nucleus slurry, the particles may be porous but have a small pore volume with a peak in the pore size distribution in the range of 1 nm to 15 nm.

[0093] Thereafter, it may be cooled (for example, to room temperature (10° C. to 30° C.)) as necessary.

[0094] Next, the hydrated ZrO 2 Adding a flocculant to the micro-crystal nucleus slurry produces hydrated ZrO. 2 A zirconium sulfate-containing basic slurry is obtained (step 3). Hydrated ZrO 2 Adding a flocculant to the micro-crystal nucleus slurry produces hydrated ZrO. 2 In order to obtain a basic zirconium sulfate-containing slurry, secondary particles having strong agglomerations between primary particles are obtained.

[0095] The flocculant is a negatively charged hydrated ZrO 2 There are no particular limitations on the material as long as it is adsorbed to the metal, and examples thereof include sodium sulfate, potassium sulfate, and aluminum sulfate (aluminum sulfate).

[0096] The type of the flocculant is preferably sodium sulfate from the viewpoint of impurities. The method of addition is not particularly limited, but examples include addition in the form of a solid or liquid. The amount of addition is preferably ZrO 2 The weight ratio to the total amount of the component (B) is preferably 0.05 or more and 1.0 or less, and more preferably 0.1 or more and 0.8 or less.

[0097] Thereafter, it may be cooled (for example, to room temperature (10° C. to 30° C.)) as necessary.

[0098] Next, the hydrated ZrO 2 A surface modifier is added to the basic zirconium sulfate-containing slurry (step 4). Hydrated ZrO 2 A surface modifier is added to the basic zirconium sulfate-containing slurry, and then a rare earth element is added (step 5), so that the aggregation of secondary particles during firing (step 7) can be suppressed. This reduces the number of agglomerates of secondary particles (tertiary particles), and most of the particles remain in the secondary particle state.

[0099] Examples of the surface modifier include oxalates, citrates, succinates, sulfates, etc. From the viewpoint of impurities, sodium oxalate and sodium citrate are preferred.

[0100] The amount of the surface modifier added is ZrO 2 The weight ratio is preferably from 0.1 to 0.8, and more preferably from 0.2 to 0.7.

[0101] Next, raw material salt containing a rare earth element is added (step 5).

[0102] The raw material salt is not particularly limited, and examples thereof include nitrates, chlorides, acetates, and hydrates of rare earth elements.

[0103] Next, the mixture is neutralized with a base to obtain a precipitate (step 6). Neutralization produces a precursor precipitate of a zirconium-containing hydroxide. The base is not limited, and examples thereof include caustic soda, sodium carbonate, ammonia, hydrazine ammonium hydrogen carbonate, etc. The concentration of the base is not particularly limited, but is usually diluted with water to a concentration of 5 to 30%.

[0104] Neutralization is carried out until the pH falls within a range of preferably 9 or more and 14 or less, more preferably 10 or more and 14 or less. This makes it possible to suitably obtain a precursor (precipitate) of the zirconium-containing hydroxide.

[0105] After neutralization, the precursor precipitate may be subjected to solid-liquid separation and washed, if necessary.

[0106] Next, the precursor precipitate is heat-treated to obtain a zirconia-based composite oxide (step 7).

[0107] The temperature of the heat treatment is preferably 400° C. or higher, and more preferably 500° C. or higher. The temperature of the heat treatment is preferably 1000° C. or less, and more preferably 900° C. or less. The temperature of the heat treatment is preferably 400° C. or higher and 1000° C. or lower, and more preferably 500° C. or higher and 900° C. or lower.

[0108] The heat treatment time is preferably 2 hours or more, and more preferably 3 hours or more. The heat treatment time is preferably 10 hours or less, more preferably 9 hours or less. The time for the heat treatment is preferably from 2 hours to 10 hours, and more preferably from 3 hours to 9 hours.

[0109] The atmosphere for the heat treatment is not particularly limited, and may be air, an inert gas (eg, nitrogen), or the like.

[0110] The heat treatment can be carried out, for example, in an electric furnace.

[0111] In this manner, a zirconia-based composite oxide can be obtained.

[0112] Furthermore, the obtained zirconia-based composite oxide may be crushed as necessary. Note that "crushing" is an operation for reducing the size of tertiary particles (operation for separating into secondary particles) by applying a separating force to an aggregate of particles, and is an operation that does not involve changes in the secondary particle size, specific surface area, or pore volume. The crushing can be carried out, for example, by a hammer mill, although the crushing is not particularly limited.

[0113] The method for producing the zirconia composite oxide powder according to this embodiment has been described above. EXAMPLES

[0114] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. Note that the zirconia-based composite oxide powder obtained in the examples and comparative examples contains 1 to 3 mass % of hafnium as an inevitable impurity relative to zirconium in terms of oxide (calculated according to the following formula (X)). <Expression(X)> ([Mass of hafnium] / ([Mass of zirconium]+[Mass of hafnium]))×100(%)

[0115] The maximum and minimum values ​​of the content of each component shown in the following examples should be considered as the preferred minimum and maximum values ​​of the present invention, regardless of the contents of other components. Furthermore, the maximum and minimum values ​​of the measured values ​​shown in the following examples should be considered as the preferred minimum and maximum values ​​of the present invention, regardless of the content (composition) of each component.

[0116] [Preparation of zirconia-based composite oxide powder] Example 1 Zirconium oxychloride octahydrate (Mitsuwa Chemical, special grade reagent, 70 g in terms of zirconium oxide) was dissolved in ion-exchanged water, and ZrO 2 The concentration was adjusted to 5% by weight. A 25% by weight aqueous solution of sodium hydroxide was added to the aqueous solution to adjust the pH to 3, and the solution was kept at 25°C for 24 hours to obtain a suspension (step 1). Hydrochloric acid was added to the suspension to adjust the pH to 1.5, and the solution was kept at 100°C for 168 hours (7 days) to obtain hydrated ZrO 2 A microcrystal nucleus slurry was obtained (step 2). After the slurry was cooled to 25° C., 150 g of a 10% aqueous sodium sulfate solution was added and kept for 1 hour to obtain hydrated ZrO 2 A zirconium sulfate-containing basic slurry was obtained (Step 3). Next, 45 g of trisodium citrate dihydrate (Wako Reagents, special grade reagent) was added (step 4). Then, cerium (III) nitrate hexahydrate (Wako Pure Chemical Industries, special grade reagent, 20 g in terms of cerium oxide), lanthanum nitrate hexahydrate (Wako Pure Chemical Industries, special grade reagent, 5 g in terms of lanthanum oxide), and yttrium (III) nitrate hexahydrate (Wako Pure Chemical Industries, special grade reagent, 5 g in terms of yttrium oxide) were added (step 5), and a 25% by mass aqueous solution of sodium hydroxide was added until the pH became 13, to obtain a precursor precipitate (step 6). The precipitate was recovered and washed by solid-liquid separation. The solid content was calcined in an electric furnace in the air at 700°C for 5 hours to obtain a zirconia-based composite oxide powder according to Example 1 (step 7).

[0117] Example 2 A zirconia-based composite oxide powder according to Example 2 was obtained in the same manner as in Example 1, except that in step 1, the pH was adjusted to 7 instead of 3.

[0118] Example 3 A zirconia-based composite oxide powder according to Example 3 was obtained in the same manner as in Example 2, except that the firing temperature in step 7 was changed to 550°C.

[0119] Example 4 A zirconia-based composite oxide powder according to Example 4 was obtained in the same manner as in Example 1, except that the firing temperature in step 7 was changed to 850°C.

[0120] Example 5 A zirconia-based composite oxide powder according to Example 5 was obtained in the same manner as in Example 1, except that in step 1, the pH was adjusted to 2.7 instead of 3, and the composition was adjusted to be as shown in Table 1.

[0121] Example 6 A zirconia-based composite oxide powder according to Example 6 was obtained in the same manner as in Example 1, except that the composition was adjusted to be as shown in Table 1.

[0122] Example 7 A zirconia-based composite oxide powder according to Example 7 was obtained in the same manner as in Example 2, except that in step 1, the pH was adjusted to 7 instead of 3, the temperature was kept at 80° C. for 24 hours, and the composition was adjusted to be as shown in Table 1.

[0123] (Example 8 to Example 10) Zirconia composite oxide powders according to Examples 8 to 10 were obtained in the same manner as in Example 1, except that the composition was adjusted to be as shown in Table 1.

[0124] Comparative Example 1 207 g of a 25% by mass aqueous solution of sodium sulfate and 438 g of an aqueous solution of zirconium oxychloride (acid concentration: 1N), which is 16% by mass in terms of zirconium oxide, were separately heated to 95°C. 4 2- / ZrO 2 The heated aqueous solutions were brought into contact with each other for 2 minutes so that the mass ratio became 0.50. Next, the obtained reaction liquid containing basic zirconium sulfate was kept at 95° C. for 4 hours for maturation, thereby obtaining basic zirconium sulfate. Next, the aged solution was cooled to room temperature, and then an aqueous solution of 10 mass % yttrium chloride in terms of yttrium oxide was added to the solution. 2 O 3 A 10% by mass cerium chloride aqueous solution, calculated as cerium oxide, was added to CeO 2 A 10% by mass aqueous solution of lanthanum chloride (calculated as lanthanum oxide) was added to La 2 O 3 was added so that the amount was 5% by weight, and mixed uniformly. Next, a 25% by mass aqueous solution of sodium hydroxide was added to the resulting mixed solution to neutralize it until the pH became 13 or higher, thereby forming a hydroxide precipitate. The obtained hydroxide precipitate was filtered and thoroughly washed with water, and the obtained hydroxide was dried for 24 hours at 105° C. The dried hydroxide was heat-treated (calcined) for 5 hours at 700° C. in the air to obtain a zirconia-based composite oxide powder according to Comparative Example 1.

[0125] Comparative Example 2 The zirconia composite oxide powder of Comparative Example 1 was mixed with the powder having a particle diameter D 50 The zirconia-based composite oxide powder according to Comparative Example 2 was obtained by wet pulverization so that the particle size was less than 1 μm. The conditions for wet milling were as follows: The unpulverized zirconia composite oxide powder of Comparative Example 1 was pulverized and mixed for 40 hours in a wet ball mill using water as a dispersion medium. Zirconia beads with a diameter of 5 mm were used for pulverization. The slurry obtained after pulverization was dried at 110°C.

[0126] Comparative Example 3 The firing temperature was changed to 1200°C, and the particle diameter D 50 A zirconia-based composite oxide powder according to Comparative Example 3 was obtained in the same manner as in Comparative Example 1, except that wet pulverization was performed so that the particle size was less than 1 μm.

[0127] Comparative Example 4 350 mL of zirconium oxychloride solution (Zr concentration = 1.6 M) (70 g in terms of zirconium oxide) and an aqueous solution of sodium sulfate (Na 2 SO 4 123 mL of an aqueous solution of sodium hydroxide (NaOH concentration = 1.6 M) was heated to 70°C, and 875 mL of an aqueous solution of sodium hydroxide (NaOH concentration = 2.5 mM) was heated to 90°C. After that, the two liquids, the aqueous zirconium oxychloride solution and the aqueous sodium sulfate solution, were mixed by liquid delivery using a constant-volume delivery pump, and the mixed liquid was then delivered directly to the aqueous sodium hydroxide solution heated to 90°C. The tubes used were made of Tygon and had an inner diameter of 4 mm, and a glass Y-shaped tube connector was used at the joining point of the two liquids for the two-liquid mixing reaction. The flow rate of the zirconium oxychloride aqueous solution was 10 mL / min, and the flow rate of the sodium sulfate aqueous solution was 3.5 mL / min. Thereafter, an aqueous solution of cerium chloride (20 g in terms of cerium oxide), an aqueous solution of lanthanum chloride (5 g in terms of lanthanum oxide), and an aqueous solution of yttrium chloride (5 g in terms of yttrium oxide) at room temperature (25° C.) were added. The mixture of the aqueous solutions was stirred at 90°C for 30 minutes, and then an aqueous sodium hydroxide solution (NaOH concentration = 0.1M) was added until the pH reached 11 or higher to obtain a slurry containing zirconium hydroxide. This was then filtered and washed with distilled water until the amount of Na and Cl contained in the precipitate was less than 100 ppm, obtaining a cake consisting of zirconium hydroxide. The collected zirconium hydroxide cake was heat-treated (calcined) in air at 700° C. for 5 hours using a box-type electric furnace. The calcined product was broken down with a hammer head (manufactured by IKA, MF10.2 hammer head) to obtain a zirconia-based composite oxide powder according to Comparative Example 4. The conditions for loosening with a hammer head were as follows: Rotational speed: 6000 rpm Sieve size: 0.5mm

[0128] [Particle diameter D 50 , D 90 Measurement of 0.15 g of the zirconia composite oxide powder of each of the examples and comparative examples and 40 ml of 0.2% aqueous sodium hexametaphosphate solution were placed in a 50 ml beaker to prepare a suspension. The suspension was dispersed using an ultrasonic homogenizer (Digital Sonifier 250, manufactured by Branson) at an oscillation frequency of 20 kHz and an output of 6000 J, and then placed in a device (laser diffraction / scattering particle size distribution measuring device (LA-950, manufactured by Horiba, Ltd.)) for measurement. The results are shown in Table 1. Regarding the dispersion conditions, by performing the dispersion treatment under the same sample amount, frequency, and output, the dispersion strength is equivalent regardless of the type of ultrasonic homogenizer.

[0129] [Pore distribution calculated from scattering curves measured by small angle X-ray scattering (SAXS)] The zirconia composite oxide powders of the Examples and Comparative Examples were measured under the following measurement conditions, and the pore distribution was obtained under the following analysis conditions. [Measurement conditions] Measurement equipment: Rigaku X-ray diffraction analyzer SmartLab Ray tube: Cu Kα Tube voltage / current: 45kV-200mA Detector: Scintillation counter Scan range: 0.06-8.00deg Scan step: 0.02deg Scan speed: 0.53deg / min [Analysis conditions] Scatterer model: sphere Measurement method: transmission method Particles / holes:Pore Matrix: CeO2 Distribution function: Gamma distribution Slit Compensation: High Analyzer crystal: None Analysis range: 0.1600~2.5000° Step: 0.0200° Wavelength: 1.541867Å Of the obtained pore distribution (measurement range 1 nm to 40 nm), the number of peaks in the range of 1 nm to 15 nm and the peak pore diameter are shown in Table 1. When there is one peak in the range of 1 nm to 15 nm and the pore diameter of the peak is 1 nm to 15 nm, it is determined that there is a monomodal distribution in the range of 1 nm to 15 nm. The pore distributions obtained in Example 1 and Example 2 are shown in Fig. 1, and the pore distributions obtained in Comparative Example 1 and Comparative Example 2 are shown in Fig. 2. Although not shown, Examples 3 to 10 also had the same pore distribution as Examples 1 and 2, and had a monomodal distribution in the range of 1 nm or more and 15 nm or less.

[0130] [Measurement of specific surface area] The specific surface area of ​​the zirconia composite oxide powders of the examples and comparative examples was measured by the BET method using a specific surface area meter ("Maxsorb", manufactured by Mountec Co., Ltd.). The results are shown in Table 1.

[0131] [Measurement of tap density] A TAPDENSER KYT-3000 (manufactured by Seishin Enterprise Co., Ltd.) was used as a measuring device for tap density. 100 g of sample powder (zirconia-based composite oxide powder according to the examples and comparative examples) was filled into a tapping cell, and the spacer height was set to 3 cm. The tapping cell was set on a tapping table, and tapping was performed 800 times with the measuring device. After tapping was completed, the scale on the cell was read, and the tap density was obtained by calculating [(powder weight) / (volume)]. More detailed measurement conditions were as follows. The results are shown in Table 1. <Conditions for measuring tap density> Tapping stroke: 3cm Tapping speed: 100 times / 50 seconds

[0132] [Measurement of bulk density] For the zirconia composite oxide powders of the Examples and Comparative Examples, the bulk density of the zirconia composite oxide powder was determined from the weight of the zirconia composite oxide powder packed into a volume of 30 ml in accordance with JIS K 5101. The results are shown in Table 1.

[0133] [Identification of crystalline phases] For the zirconia composite oxide powders of the examples and comparative examples, X-ray diffraction spectra were obtained using an X-ray diffractometer ("Ultima IV" manufactured by Rigaku Corporation). The measurement conditions were as follows. <Measurement conditions> Measurement equipment: X-ray diffraction equipment (Rigaku, Ultima IV) Source: CuKα source Tube voltage: 50kV Tube current: 30mA Scanning speed: 2θ=20~80°: 4° / min

[0134] Then, the crystal phase was identified from the X-ray diffraction spectrum. When the zirconia-based composite oxide contains tetragonal and / or cubic crystals, peaks derived from the tetragonal phase (101) plane and the cubic phase (111) plane appear around 28.5 to 31°. On the other hand, when the monoclinic crystals are contained, peaks derived from the monoclinic phase (-111) plane appear around 28° and the monoclinic phase (111) plane appear around 32°. When there are peaks around 28° and 32°, it was determined that the sample contains monoclinic crystals, and when there are peaks around 28.5 to 31°, it was determined that the sample contains tetragonal and / or cubic crystals. The results are shown in Table 1.

[0135] [HAADF-STEM image observation using a transmission electron microscope] For the zirconia-based composite oxide powders of the examples and comparative examples, a high-angle scattering annular dark-field scanning transmission microscope image (HAADF-STEM image) was obtained using a transmission electron microscope ("JEM-ARM200F" manufactured by JEOL Ltd.) under the condition of an acceleration voltage of 200 kV. FIG. 3 is a HAADF-STEM image of Example 1. FIG. 4 is a HAADF-STEM image of Example 2. FIG. 5 is a HAADF-STEM image of Comparative Example 1. Although not shown, HAADF-STEM images were obtained in the same manner for other examples and comparative examples. The obtained images were observed according to the following <Procedure> to confirm whether or not pores exist within a single particle. As a result, the zirconia-based composite oxide powders of the examples had pores within a single particle. On the other hand, the zirconia-based composite oxide powders of the comparative examples did not have pores within a single particle. <Procedure> a. Take a HAADF-STEM image at 2 million times magnification or more. b. Convert to grayscale (8-bit) using image analysis software. c. Areas with a brightness value of 80 or more, expressed in 256 levels from 0 to 255, are determined to be areas containing particles, and a single spherical particle with no overlapping particles is extracted. d. Within the extracted particles, regions with a long axis of 1 nm or more where the brightness value is 40% or more lower than the surrounding area are considered to be pores, and their presence or absence is confirmed. e. Repeat until the cumulative number of particles confirmed to have pores reaches 100. f. If it is confirmed by steps a to e that all particles have pores in them, it is determined that the particles have pores in them.

[0136] [Table 1]

Claims

1. Zirconia and Oxides of rare earth elements Including, The content of the zirconia is 50% by weight or more and 95% by weight or less, In the pore distribution calculated from the scattering curve measured by small angle X-ray scattering, the pore size distribution is monomodal in the range of 1 nm to 15 nm, Particle diameter D in particle size distribution measured by laser diffraction / scattering method 50 is 0.05 μm or more and less than 1.0 μm, Tap density is 1.0 g / cm 3 1.7g / cm or more 3 is as follows: A zirconia-based composite oxide powder, characterized in that the crystal system identified by powder X-ray diffraction is either a tetragonal system, a cubic system, or both.

2. 2. The zirconia composite oxide powder according to claim 1, characterized in that each particle has a pore therein.

3. The particle diameter D 50 3. The zirconia composite oxide powder according to claim 1, wherein the average particle size is 0.08 μm or more and 0.85 μm or less.

4. Specific surface area is 30m 2 / g or more 90m 2 3. The zirconia composite oxide powder according to claim 1, wherein the zirconia composite oxide powder has a molecular weight of less than 1.0 / g.

5. the rare earth oxide is at least one selected from the group consisting of yttrium oxide, lanthanum oxide, cerium oxide, neodymium oxide, and praseodymium oxide; 3. The zirconia composite oxide powder according to claim 1, wherein the content of the oxide of the rare earth element is 5% by weight or more and 50% by weight or less.

6. Step 1: adjusting the pH of an aqueous solution of zirconium oxychloride to form a suspension; The pH of the suspension is made lower than that of step 1, and the suspension is heated to obtain hydrated ZrO 2 Step 2 of obtaining a microcrystal nucleus slurry; The hydrated ZrO 2 Adding a flocculant to the microcrystal nucleus slurry to produce hydrated ZrO 2 Step 3 of obtaining a zirconium sulfate-containing basic slurry; The hydrated ZrO 2 Step 4 of adding a surface modifier to the zirconium sulfate-containing basic slurry; Step 5 of adding a raw material salt containing a rare earth element; Step 6: neutralizing with a base to obtain a precipitate; a step 7 of obtaining a zirconia-based composite oxide by heat-treating the precipitate; 3. The method for producing a zirconia-based composite oxide powder according to claim 1, further comprising the steps of:

Citation Information

Patent Citations

  • Zirconia fine powder and method of manufacturing the same

    JP2006240928A

  • Powder consisting of oxide microcrystal particles, catalyst using it, and its manufacturing method

    JP2007217265A

  • Catalyst carrier for modification and its preparing method

    JP2008246416A

  • Metal oxide composite material and purification catalyst using the same and method for producing these

    JP2013014458A

  • Zirconia-based powder material

    JP2023142376A